Hawking Radiation from the Boundary Scalar Field and the Information Loss Paradox - Jingbo Wang (Universe, 2023)
Hawking radiation is an essential property of the quantum black hole. It results in the information loss paradox and provides an important clue with regard to the unification of quantum mechanics and general relativity. In previous work, the boundary scalar fields on the horizon of black holes were used to determine the microstates of BTZ black holes and Kerr black holes. They account for Bekenstein–Hawking entropy. In this paper, we show that the Hawking radiation can also be derived from those scalar fields. Hawking radiation is a mixture of the thermal radiation of right- and left-moving sectors at different temperatures. Based on this result, for static BTZ black holes and Schwarzschild black holes, we propose a simple solution for the information loss paradox; i.e., the Hawking radiation is pure due to its entanglement between the left-moving sector and the right-moving sector. This entanglement may be detected in an analogue black hole in the near future.